(untitled) (The Gaze: Journal of Tourism and Hospitality, 2018)
In course of designing the courses, the present author in the phase of curriculum coordination, consulted various research papers and books based on the theoretical models of tourism and hospitality education. The review of those works not only have broadened the mind of curriculum designer but also has given knowledge education on various fields of tourism education. It is strongly believed that tourism education will become the backbone and impetus for making tourism as an institution and industry stronger. One of the most important aspects of studying tourism is disciplinarian approach. The sources of knowledge production are based on monodiscipline, multidiscipline, interdiscipline, transdiscipline, extradiscipline, postdiscipline, antidiscipline, metadiscipline and nomadology also coined as disciplinary pluralism or plurydisciplines that have created a disciplinary dilemma. The curriculum should be designed on the basis of praxis and phronesis (Aristotalian thought based on application and theory), Tourism Education Future Initiative’s ( TEFI ) model, John Tribe’s (1997) model ( TF1 and TF2) , Echtner’s (1995) three pronged approach, Mayaka and Akama’s (2007 & 2015) curriculum space model and Koh’s (1994) marketing approach and others. All the above mentioned theoretical models and approaches will help in thinking of and thinking for tourism and hospitality. Simultaneously, it will also help for knowing, seeing, doing and being in the field of education in relation with tourism, hospitality and events (THE). But in this study, only tourism education has been prioritized. Tourism academic world has debated and advocated regarding different approaches, concepts, models, theories and paradigms developed by different scholars of tourism and hospitality. The scientific and reliable arguments have been occurred in different timelines, centralized on tourism education, research, knowledge, phenomena, normative and existential knowledge, successful intelligence, learning, life-long learning, collaboration, professionalism competences, scholarship, disciplines, academic territory, academic tribe, field, forcefield, studies, knowledge production, philosophic practitioner, curriculum space, management, social sciences, disciplinary pluralism, liberal and vocational balance in the field of tourism and hospitality subjects that have become the force for understanding tourism education in a better way. The Gaze: Journal of Tourism and Hospitality Vol.9 2018 p.83-155